Individual and family labor market impacts of chronic diseases - Amanda Gaulke (IZA World of Labor, 2021)
Chronic health conditions are a global concern and can impact labor market outcomes of those diagnosed and their caregivers. Since the global prevalence of many chronic health conditions is on the rise, it is important to know what firms can do to retain and hire workers who are impacted. Firms can improve hiring by addressing biases against potential employees with chronic health conditions. Furthermore, firms can retain impacted workers by offering workplace flexibility such as partial sick leave, work hour flexibility, and part-time work options.
Keywords: J22; J23; M51; I14; J14; 330; chronic health conditions; labor supply; earnings; caregivers